A Review of Antimicrobial Materials for Use in Respiratory Face Masks - Imran, Abdullah; Javeed Shaikh, Mohammed; Sharifatul Ain, Sharifuddin; Irfan, Mohamad (2016)
Million of Muslims of vast ethnic diversities congregate in Mecca every year to perform Umrah and the Hajj. Pilgrims are highly vulnerable to airborne transmitted diseases during these periods. Several preventive measures are being taken to reduce the spread of airborne diseases, especially those caused due to respiratory. tract infections.· One of the preventive measures being taken is by recommending the use of face masks for respiratory tract protection. The use of respiratory face masks has been shown to reduce the spread of respiratory diseases, especially when used by individuals in confined areas or in close contact with a person with influenza-like Symptoms. This review is focused on antimicrobial materials which are currently being used or have potential to be used in respiratory face- masks. The materials reviewed here include activated carbon fiber and various .metal nanoparticles. Metal nanoparticles represent a new class .of important materials that are increasingly being used as antimicrobial agents against several microorganisms including fungi, yeast and both gram-positive and gram-negative bacteria. The impregnation of metal nanoparticles into existing or new materials used in manufacturing respiratory face masks is believed to potentially prevent respiratory tract infections.